Weighted evidence combination based on degree of credibility and certainty - Lu WANG; Qing-hua XING; Yi-fan MAO (Tongxin xuebao)
To overcome the invalidation problem of Dempster rule with high conflict,a weighted combination method based on degree of credibility and certainty was proposed.Firstly,the cosine similarity was modified to hold the ability to measure the evidence conflict when multi-subset focal elements were included,followed by the building of evidence credibility model.Secondly,the evidence certainty model based on precision and entropy was presented,which can both reflect the evidence’s degree of multi-subset focal elements and the dispersion degree of probability assignment.Then the weighted coefficient was determined by credibility and certainty.Finally,the normalized weighted coefficient was used to average the basic probability assignment,and the final combination result can be obtained according to Dempster rule.Numerical examples show that,compared with other traditional weighted combination methods,the proposed approach has made better performance in reducing conflict and accelerating convergence.